Sikap Politik Petani dalam Pilkada Kabupaten Semarang 2015 di Kelurahan Pringapus Kecamatan Pringapus - Ladini, Malisa (Universitas Negeri Semarang, 2017)
Political farmers in the elections of 2015 in Semarang Sub District Pringapus reflect developments in the political consciousness. This study aimed to political attitudes of farmers in the village Pringapus in the elections of 2015 to the Semarang political parties/coalition of political parties and candidates stretcher couple Cabup/regent. The study used a qualitative approach, the research background Pringapus Village, the focus of research in political attitudes of farmers towards political parties/coalition of political parties and candidates stretcher couple Cabup/regent, the primary data source for farmers, Team Winning Candidate 1, Candidate 2 Success Team, secondary data is written and photographs data collection techniques of observation, documentation, interviews with technical validity of the data triangulation techniques, triangulation, data analysis techniques interactions. The results that the farmers in the village Pringapus active in Farmers have a political stance against the political parties/coalition of political parties and candidates stretcher couple Cabu/regent in the elections of 2015 Semarang better knowledge and understanding of the political parties Cabup/regent, his emotions like the political parties and Cabup/regent, and conative choose political parties and Cabup/cawabup cares farmers, but the farmers who are not active in the farmers Group has a political stance worse, yet his knowledge and understanding of the political parties Cabup/regent, his emotions did not like the performance of political parties and Cabup/regent, conative and confusion. Saran, the need for a more intense approach of Political Parties and Candidates Regent/Vice Regent of the peasantry.